2005
DOI: 10.2166/wst.2005.0472
|View full text |Cite
|
Sign up to set email alerts
|

Investigating helminth eggs and Salmonella sp. in stabilization ponds treating septage

Abstract: Sludge management arises as a relevant problem after being accumulated in primary ponds of septage treatment plants. One of the most attractive options for sludge disposal is its use in agriculture and then specific guidelines regarding hygienic quality must be fulfilled. This study aimed at evaluating the storage time needed to inactivate Ascaris eggs and Salmonella in sludge accumulated in a primary pond treating septage. Raw septage exhibited very low concentrations of viable Ascaris eggs, thus experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 3 publications
4
13
0
6
Order By: Relevance
“…The fact that we were able to observe nematode eggs, ranging from resistant ( Trichuris eggs, Sanguinetti et al, 2005) to more fragile (strongylid eggs, Waruiru et al, 1998), supports the efficacy of RNA later ® as a preservation method. The observation of Troglodytella was also particularly interesting, demonstrating that it is possible to identify a ciliate trophozoite (which is a more fragile cellular element compared to parasite cysts or thick-walled helminth eggs) in samples stored in RNA later ® .…”
Section: Discussionsupporting
confidence: 66%
“…The fact that we were able to observe nematode eggs, ranging from resistant ( Trichuris eggs, Sanguinetti et al, 2005) to more fragile (strongylid eggs, Waruiru et al, 1998), supports the efficacy of RNA later ® as a preservation method. The observation of Troglodytella was also particularly interesting, demonstrating that it is possible to identify a ciliate trophozoite (which is a more fragile cellular element compared to parasite cysts or thick-walled helminth eggs) in samples stored in RNA later ® .…”
Section: Discussionsupporting
confidence: 66%
“…They have high resistance to chemical and physical conditions such as lime, ammonia, temperature, and as such they are the most resistant form of parasites. Studies have revealed that Ascaris eggs can survive under high moisture content in biosolids stored in the environment (Whanton 1979;Stromberg 1997;Sanguinetti et al 2005), but when biosolids are dried, it speeds up the desiccation rate of Ascaris eggs, reducing egg survival (Feachem et al 1983;Gaspard & Schwartzbrod 2003;Cappizzi-Banas et al 2004). Studies have revealed that Ascaris eggs can survive under high moisture content in biosolids stored in the environment (Whanton 1979;Stromberg 1997;Sanguinetti et al 2005), but when biosolids are dried, it speeds up the desiccation rate of Ascaris eggs, reducing egg survival (Feachem et al 1983;Gaspard & Schwartzbrod 2003;Cappizzi-Banas et al 2004).…”
Section: A Larger Pathogen Reduction Was Recorded In the Biosolids Frmentioning
confidence: 99%
“…The eggs are difficult to inactivate [3] and can survive for long periods of time (e.g. 20 months) in pond treatment [4]. An effective treatment using x-ray irradiation would be highly advantageous for the disinfection of municipal biosolids.…”
Section: Ascaris Eggsmentioning
confidence: 99%